Is Community Pharmacies' Personnel Well-Oriented about Cosmeceuticals? A Cross-sectional Survey and Costumer Simulation. - Nazila Yousefi; Hesam Noqani; Ghader Mohammadnezhad; MohammadJavad Foroughi; Farzad Peiravian (Research Center for Rational Use of Drugs (RCRUD), 2024)
Background The cosmetics business is one of the most profitable and advanced global trade sectors, and academic and industrial investments have expanded to provide high-quality products to the right consumers. Thus, this cross-sectional survey assessed Iranian pharmacists and pharmacy technicians' cosmetic product knowledge, attitudes, and behaviors. Methods Demographics were the first questionnaire section after eligibility and consent. Ten questions test knowledge in the second phase. The third portion has nine pharmacist cosmetic product attitudes questions. We used five-point Likert spectrum scaling. The final component of the questionnaire includes a pharmacist practice checklist. This fulfilled 12 pharmacists' obligations. PT demographics, knowledge, and attitude were measured using an eight-, five-, and eight-item questionnaire. A cosmetic sales checklist with eight practice items was devised to evaluate PTs. Pharmacists and PTs were evaluated for scientific advice on exfoliating lotion and anti-stain sunscreen use, skin type, history, and brand presentation. Using a 95% confidence interval, binary logistic regression found significant relationships between categorical dependent and independent variables. Pearson correlation measured knowledge-performance linearity. Results The study included 325 pharmacists and 324 PTs. The average knowledge score for pharmacists was 6.38 ± 1.95, while their practice score was 6.35 ± 1.92 out of 10. The overall knowledge score for PTs was 2.8 ± 0.92 out of 5. Results indicate a strong association between pharmacist and PT knowledge and cosmeceutical performance (r= +0.635 and +0.564, respectively, P < 0.001). Conclusion  This study indicates a strong correlation between knowledge and performance in community pharmacists and PTs.